Pengaruh Discovery Learning Terhadap Peningkatan Hasil Belajar Matematika Dan Keterampilan Berpikir Kritis Siswa Sekolah Dasar - Mohamad Azhar Annawa UBM; Nur Ifan Syah; Wulan Feronika Maharani (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
Because of traditional and passive teaching methods in mathematics, most people view math as a strange and uninteresting subject. Discover Learning as a student-centered learning method is easily seen where the answers come from; it simply allows students to explore topics on their own. The higher their participation in teaching, the more it supports them in thinking critically. The research method is a qualitative literature review, based on various studies on the use of Discover Learning in mathematics teaching. Data analysis was conducted to assess this approach for learning interest and to test students' critical thinking skills. This research found that, in addition to deepening students' understanding of mathematical concepts, Discover Learning encourages them to be more active in their learning. Elementary school students may benefit from Discovery Learning as this approach also supports cognitive growth in line with their developmental stage. However, there are several obstacles to implementing this strategy, including a lack of resources, time, and differences in students' learning styles. However, as long as teachers make the necessary modifications, discovery learning may still be a useful strategy to enhance the quality of mathematics teaching.